PENGARUH PROFESIONALISME DAN INDEPENDENSI TERHADAP PENCEGAHAN KECURANGAN DENGAN IKLIM ETIKA-EGOISME SEBAGAI VARIABEL MODERASI - Wijaya, Christine Lie; Adechandra A. P, David (Jurnal Ilmu Sosial dan Humaniora, 2020)
Fraud prevention is needed for companies so that fraud does not occur. This is influenced by the attitude of professionalism and independence possessed by internal auditors. This study aims to analyze the effect of professionalism and independence on the prevention of fraud by using a moderating variable that is the ethical climate-egoism. Data obtained from employees at PT. X which is engaged in the pharmaceutical field. Samples obtained by the saturation sampling method is 60 samples. The results show that professionalism has a positive effect on fraud prevention, while independence has a negative effect on fraud prevention. Ethical climate-egoism as a moderating variable strengthens the relationship between professionalism and independence with fraud.